Apprenticeship in a globalised world : premises, promises and pitfalls - Akoojee, Salim [Herausgeber]; Gonon, Philipp [Herausgeber]; Hauschildt, Ursel [Herausgeber]; Hofmann, Christine [Herausgeber] (Lit-Verlag, 2013)
"In April 2013, the International Network on Innovative Apprenticeship (INAP) hosted its fifth international conference in Johannesburg, South Africa, in co-operation with the International Labour Organisation (ILO). Bringing together researchers, policy makers and practitioners from more than 34 countries, the conference pointed the need for apprenticeships to deliver on its promise of workplace skills and for it to respond to changing economic and social realities. This book is a summary of papers presented and discussed at the Johannesburg Conference split up equally to the five key areas: (1) Introducing Apprenticeship: Backgrounds, changes and difficulties; (2) Enabling learning opportunities in workplaces and informal contexts; (3) Competence assessment and development; (4) Managing transitions from VET into the world of work; (5) Curriculum design, apprenticeships and National Qualification Frameworks." With regard to the conference venue, a particular focus was on topics that refer to the African context. One of the most central issues here is the question, how informal apprenticeship systems can be upgraded. (Autorenreferat, BIBB-Doku)
Keywords: S System beruflicher Bildung; Berufsbildungssystem; Lernen am Arbeitsplatz; Berufsausbildung; Informeller Sektor; Kompetenzentwicklung; Kompetenzbewertung; Berufseinmündung; Zweite Schwelle; Qualifikationsrahmen